2008
DOI: 10.1007/s12291-008-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and ameliorative potential of Ficus bengalensis bark extract in streptozotocin induced diabetic rats

Abstract: The aim of the present study was to evaluate the antidiabetic and ameliorative potential of aqueous extract of Ficus bengalensis bark in streptozotocin induced diabetic rats. The effect of oral administration of aqueous extract of F. bengalensis bark on blood glucose, serum electrolytes, serum glycolytic enzymes, liver microsomal protein, hepatic cytochrome P-450 dependent monooxygenase enzymes and lipid peroxidation in liver and kidney of streptozotocin -induced diabetic rats was studied. Oral administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 28 publications
(23 reference statements)
3
28
0
Order By: Relevance
“…Intraperitoneal administration of streptozotocin effectively induced diabetes in normal rats, as observed by hyperglycemia when compared with normal rats. Persistent hyperglycemia, the common characteristic of diabetes can cause most diabetic complications and it is normalized by the action of insulin (Gayathri and Kannabiran, 2008). In the present study, it was observed that oral administration of SAC could reverse the above mentioned diabetic effect, possibly due to an insulinlike effect of SAC on peripheral tissues, either by promoting glucose uptake and metabolism, or by inhibiting hepatic gluconeogenesis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Intraperitoneal administration of streptozotocin effectively induced diabetes in normal rats, as observed by hyperglycemia when compared with normal rats. Persistent hyperglycemia, the common characteristic of diabetes can cause most diabetic complications and it is normalized by the action of insulin (Gayathri and Kannabiran, 2008). In the present study, it was observed that oral administration of SAC could reverse the above mentioned diabetic effect, possibly due to an insulinlike effect of SAC on peripheral tissues, either by promoting glucose uptake and metabolism, or by inhibiting hepatic gluconeogenesis.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that STZ-induced diabetes produces partial or total deficiency of insulin that results in decreasing the activity of glycogen synthase and increasing the activity of glycogen phosphorylase (Gayathri and Kannabiran, 2008) leads to decreasing the storage of tissue glycogen (Senthil Kumar et al, 2006). Administration of SAC and glyclazide to diabetic rats restored the level of liver glycogen by decreasing glycogen phosphorylase activity and increasing glycogen synthase activity.…”
Section: Groupsmentioning
confidence: 99%
“…It is used in diabetes, diarrhea, leucorrhoea, menorrhea, nervous disorder, vaginal diseases, in the treatment of skin diseases, ulcer and soreness in the mouth etc. [30,31]. F. virens possess antioxidant properties [32][33][34] and do not show any toxicity even at higher and repeated doses [35].…”
Section: Introductionmentioning
confidence: 99%
“…This could be the reason for the altered electrolyte balance in diabetic rat, which resulted in the elevated serum sodium, potassium and calcium in STZ-induced diabetic rats. However, administration of 28-HC reduced the glucose level and restored tissue electrolytes and this can be the possible cause for the reduction of the serum electrolytes levels [16].…”
Section: Discussionmentioning
confidence: 98%